Prototypical Predicates Have Unmarked Phonology - Jennifer L. Smith (Amherst demo, 2014)
Recent work recognizes that phonological processes and phonotactics can be sensitive to lexical category. Moreover, there are strong cross-linguistic tendencies concerning the nature of phonological differences between categories. One such tendency is a hierarchy of phonological privilege, N > A > V: nouns tend to license more phonological contrasts and tolerate more marked structures than adjectives, with verbs showing the least privilege and therefore the greatest phonological unmarkedness. This paper proposes that the N > A > V hierarchy of phonological privilege derives from a more general scale, according to which protypical designators (or arguments) have more phonological privilege, and prototypical predicates show greater unmarkedness. This approach predicts that even within a given lexical category, such as V, category members that are more prototypical as predicates should show greater unmarkedness. A case study is presented in support of this proposal. In Tokyo Japanese, unergative verbs (more-prototypical predicates) show greater phonological unmarkedness with respect to pitch accent than unaccusative verbs (less-prototypical predicates). Some preliminary implications of this finding for our understanding of lexical-category effects in phonology, and of the role of markedness scales in the grammar, are also considered.
Keywords: lexical categories; Markedness Scales; Tokyo Japanese; pitch accent; Unergative Verbs